Developmental trajectories of conditional parental regard and long-term association with students’ academic functioning - Bouffard, Thérèse; Marquis-Trudeau, Audrey; Bonneville-Roussy, Arielle; Vezeau, Carole; Pansu, Pascal (Frontiers in Education, 2023)
To feel unconditional love and acceptance from parents is a need which fundamental character is widely recognized. This article presents the results of a longitudinal study which first objective is to identify trajectories of change in perceived parental support conditional on academic success over a five-year period. The second objective examines whether students' gender, mental ability, and parental education predict membership in the trajectories and the third examines whether students' academic functioning differs according to their membership to different trajectories one year later, when they were in Secondary 5. A sample of 776 students (371 males) reported their perception of conditional parental support yearly from grade 6 to secondary 4. In secondary 5, they answered a questionnaire on their academic motivation, self-regulation, test anxiety and intention to drop out. Teachers also reported their perceptions of the participating students' academic motivation and self-regulation and rated their academic performance. Results of latent class growth analysis (LCGA) shows that the most optimal model identified three patterns of change in students' perceptions of their parents' conditional support. Students' gender, mental ability, and parental education do not predict membership in trajectories. Results of the BCH procedure indicate that whether self-reported or teacher-reported, the academic functioning of students in the low perceived conditional support trajectory was superior to that in the other two trajectories. These results add evidence that parents can have a long-term impact on children's academic functioning and underscore the need to educate parents about the importance of avoiding associating their support and regard with their child's academic performance.